Forming method of hollow special-shaped carbon fiber composite material
By chemically modifying the original sand and building a high-strength coating layer, combining special adhesives and coating systems, a sandy core mold is prepared using 3D printing technology, which solves the problems of difficult manufacturing, complex demolding and high cost of hollow special-shaped carbon fiber composite core molds, and achieves an efficient and environmentally friendly molding process.
Patent Information
- Application Number
- CN202510027985.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-08
AI Technical Summary
In the prior art, when preparing hollow special-shaped carbon fiber composite materials, the manufacturing of the core mold is difficult, the mold release process is complex and the cost is high, and the core mold material is difficult to recover, which poses a risk of environmental pollution.
By chemically modifying the original sand, building a high-strength coating layer, and designing a special adhesive and coating system, a sand core mold is prepared using 3D printing technology to achieve rapid collapse and mold removal.
It improves the strength and collapse of the sand core mold, simplifies the mold release process, reduces production costs, and improves the recycling rate of materials and reduces environmental pollution.
Smart Images

Figure CN119820898A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of carbon fiber composite materials, and in particular to a molding method of a hollow special-shaped carbon fiber composite material. Background Art
[0002] Carbon fiber composite material is a high-performance composite material with carbon fiber as reinforcement and resin, metal, ceramic, etc. as matrix. It has excellent properties such as low density, high strength, high modulus, impact resistance, fatigue resistance, high temperature resistance, and corrosion resistance. Carbon fiber composite materials have been widely used in the automotive, rail transportation, marine and wind energy industries due to their high specific modulus and high specific strength. Especially in the aerospace field, carbon fiber composite materials are widely used in fuselage structures to effectively reduce weight and improve performance. With the extensive application of carbon fiber composite materials in the aerospace field, many requirements have been put forward for the shape of carbon fiber composite materials, such as hollow and special-shaped.
[0003] At present, the preparation methods of hollow special-shaped carbon fiber composite parts mainly include autoclave molding, winding molding, injection molding, pultrusion molding, stamping molding, etc. These methods all require mold support, and the design and development of the mold becomes the key. It is necessary to consider factors such as mold material, structure and precision, process and economy to ensure the dimensional accuracy, surface finish and mechanical properties of the product, while reducing production costs.
[0004] At present, the methods for preparing the core mold required for hollow special-shaped carbon fiber composite materials include hard plastic foaming method, soft plastic foaming method, low melting point alloy method, inflatable airbag method, etc. For the hard and soft plastic foaming method, the generation and diffusion of gas during the foaming process will affect the dimensional accuracy and shape stability of the final core mold, and it is difficult to ensure the molding of high-quality carbon fiber composite materials. For the low melting point alloy method, due to the fluidity and solidification characteristics of the alloy during the melting process, local alloy accumulation or vacancies may occur, making it difficult to accurately control the shape and size of the product, which ultimately affects the quality and appearance of the carbon fiber composite product. The precision of the inflatable airbag method is relatively limited. The airbag will deform during the inflation process under the action of the mold, and it is difficult to accurately control the shape and size, which has a great impact on the molding accuracy and appearance quality of carbon fiber composite products. After the carbon fiber composite material is molded by the core mold obtained by the hard plastic foaming method, soft plastic foaming method, low melting point alloy method, inflatable airbag method, etc., a complex demoulding mechanism or additional power and energy are usually required to complete the demoulding process, which is very easy to cause serious damage to the carbon fiber composite material product during the demoulding process, resulting in an increase in the scrap rate of the product, affecting the yield rate, and at the same time, invisibly greatly increasing the production cost. At the same time, the hard plastic foaming method involves specific hard plastic resins and chemical foaming agents and other materials. The recycling of these materials is relatively difficult, especially the hard plastic products after foaming treatment. The structure is complex and it is difficult to effectively separate and recycle different components. In addition, some chemical foaming agents may have potential environmental hazards and may cause pollution to the environment. Due to their special physical properties, soft foaming materials are difficult to effectively separate and reprocess during the recycling process, requiring special recycling equipment and complex process flows. Some chemical foaming agents may remain in the foamed products, causing certain impacts on the environment. The low-melting alloy method uses low-melting alloy materials. Although they are recyclable to a certain extent, the recycling of alloy materials usually requires specific equipment and high temperature conditions. The difficulty of recycling after doping increases significantly, making the recycling process complicated and costly. The inflatable airbag method mainly relies on airbag materials, such as rubber, nylon fabric composite rubber, etc. These materials have certain limitations in recycling and processing. After long-term use or abandonment, materials such as rubber may be difficult to effectively recycle and reuse due to aging, wear and tear, etc., and the airbag structure is relatively complex, and it is also difficult to disassemble and separate different components.
[0005] The preparation and application defects of the above core molds are mainly concentrated in three aspects, namely the difficulty of manufacturing complex-shaped core molds, the difficulty of demolding complex-shaped core molds after the hollow special-shaped carbon fiber composite materials are formed, and the problem of recycling and reuse of core mold materials. First of all, in order to obtain core molds of complex shapes, special molds need to be developed. The difficulty and cost of developing complex-shaped molds are extremely high: in the process of using molds to manufacture core molds, the core molds need to withstand high-intensity impact forces, so materials with high hardness and toughness need to be selected for production; in order to ensure processing accuracy and surface finish, strict quality control and inspection of raw materials are also required; in addition, the design and manufacture of core molds need to consider the uniformity of vibration frequency and amplitude during the manufacturing process to avoid quality problems caused by uneven force. The difficulty of manufacturing limits the development and development of complex-shaped core molds. Secondly, demoulding the complex-shaped core mold after the hollow special-shaped carbon fiber composite material is formed is also a major challenge. In the overall molding process of the hollow special-shaped carbon fiber composite material, most of the core molds made of low-melting-point alloys are used (for example, the patent document with the publication number CN107599445A). After solidification, it is necessary to melt to achieve demoulding. This process requires precise control of temperature and time to ensure the integrity of the composite material structure. At the same time, the production cost is extremely high, and the shape and size of the moldable carbon fiber composite material are greatly limited. Finally, the core mold material is difficult to recycle and reuse, which wastes resources and is easy to cause harm to the environment on the one hand, and greatly increases the production cost on the other hand.
[0006] 3D printing technology uses bondable materials such as metal, plastic, ceramic, sand and gravel to build three-dimensional objects by stacking them layer by layer. 3D printing uses sand as the raw material, which is cheap and easy to obtain, greatly reducing the cost of mold production. Due to the intervention of computer-aided design, 3D printing technology has greater design freedom, making it feasible to manufacture molds with complex geometric structures and internal space structures. Despite this, the adhesive system currently used in sand mold 3D printing is usually composed of resin and curing agent. The above-mentioned resin-cured and bonded sand molds often have higher strength, and because the cured resin is insoluble in water, conventional 3D printed sand molds cannot collapse when exposed to water, which is not convenient for the subsequent separation and removal of carbon fiber composites and sand core membranes. Therefore, the application of 3D printed sand molds in the field of hollow special-shaped carbon fiber composite molding is greatly limited.
[0007] Based on the above difficulties, how to utilize technological innovations in raw sand, adhesive systems and coatings, combined with 3D sand printing adhesive jetting technology to design a demoldable sand core mold that can meet the subsequent processing strength requirements, does not adhere to carbon fiber composite materials and can quickly collapse, has become the key to the application of 3D printed sand molds in the field of hollow special-shaped carbon fiber composite molding. Summary of the invention
[0008] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a method for forming a hollow special-shaped carbon fiber composite material.
[0009] The technical solution of the present invention to solve the technical problem is to provide a method for forming a hollow special-shaped carbon fiber composite material, characterized in that the method comprises the following steps:
[0010] Step 1: chemically modify the raw sand to arrange the chemical groups and structure on the surface of the raw sand; then wash to remove impurities and unreacted substances on the surface, and then dry to obtain modified sand;
[0011] Step 2, adding the resin curing catalyst solution to the modified sand, mixing evenly, to obtain modified sand containing the catalyst; then adding the water-soluble polymer, mixing evenly, to obtain a mixed system of the resin curing catalyst solution, the water-soluble polymer and the modified sand; then drying the mixed system while stirring to remove moisture and promote the coordination reaction to be complete, while improving the catalytic activity of the resin curing catalyst, and coating the surface of the modified sand with the water-soluble polymer to obtain coated sand with a core-shell structure in which the shell layer is the water-soluble polymer and the core layer is the modified sand;
[0012] Step 3: using the resin adhesive and the coated sand of step 2 as raw materials, a sand core mold is prepared by compression molding or 3D printing;
[0013] Step 4, compounding a liquid penetration barrier coating on the outer surface of the sandy core mold in step 3, and then compounding a resin matrix penetration barrier and adhesion barrier coating on the surface of the liquid penetration barrier coating to improve the surface structure and roughness of the sandy core mold, and at the same time constructing a coating on the surface of the sandy core mold to prevent liquid resin from penetrating during molding of the carbon fiber composite material, thereby obtaining a coated sandy core mold;
[0014] Step 5, using the coated sand core mold of step 4 as a molding mold for the carbon fiber composite material, and performing a carbon fiber composite material molding process; after the resin is solidified, using a solvent that can dissolve the water-soluble polymer of step 2 to collapse the molding mold, completing the demolding process, and obtaining a hollow special-shaped carbon fiber composite material.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] (1) Based on the optimization of the surface structure and groups of raw sand from various sources by chemical modification, the present invention constructs a high-strength coating layer on the surface of raw sand from various sources based on the coordination effect between soluble metal salts and polymers and the interaction between polymers and the surface structure and groups of raw sand from various sources. The above innovations have the following effects: First, repairing the defects of the surface of raw sand from various sources serves to greatly improve the strength of the sand core film, which is an important prerequisite for the application of the sand core film; second, establishing a soluble shell layer serves to disintegrate the sand core film, which is a necessary condition for the sand core film to be used as a hollow special-shaped carbon fiber composite material molding mold; third, the coordinated metal salt provides catalysis for the subsequent curing of the adhesive, which is a guarantee for the sand core film to be formed by manual or 3D printing technology; fourth, the coated sand has low regain, excellent fluidity and uniform particle size distribution, which provides support for its application in the sand laying system of industrial-grade 3D sand printers.
[0017] (2) The present invention designs a special adhesive, the viscosity and surface tension of which match the requirements of the industrial-grade 3D sand printer nozzle, and the inkjet process can be completed continuously and stably through the nozzle system. After the sprayed adhesive contacts the coated sand in the sand-laying system, the coordinated metal salt in the coating layer catalyzes the adhesive to undergo a curing reaction, and the cured adhesive bonds the coated sand into an integral structure by point bonding. Based on the characteristics that the designed adhesive and the coated sand are suitable for molding on a 3D sand printer, the industrial-grade 3D sand printer can accurately print various complex and special-shaped sand molds to obtain sand core membranes of various complex shapes, which can greatly provide special mold support for the molding of hollow special-shaped carbon fiber composite materials.
[0018] (3) The present invention designs a special formula coating for optimizing the surface characteristics of the sand core mold. The surface of the sand core mold is processed and optimized by coating superposition or composite coating, which fills the defects of the surface of the sand core mold, gives the core mold a smoother surface, and can effectively block the infiltration of resin during the molding process of the carbon fiber composite material, thereby preventing the core mold from sticking to the carbon fiber composite material, so that the prepared carbon fiber composite material has excellent surface finish. In addition, the excellent compressive and tensile strength of the sand core mold effectively guarantees the high-quality molding of the carbon fiber composite material.
[0019] (4) The present invention is more advanced in demolding method for manufacturing sand core molds. The coated sand shell layer in the core mold of the present invention has excellent solubility. After the hollow special-shaped carbon fiber composite material is formed, based on the mechanism of "without the skin, where will the hair be attached", the coated sand shell layer can be dissolved to destroy the bonding points constructed by the adhesive on the shell layer, so that the sand core mold is completely collapsed, thereby easily achieving the demolding goal. This demolding method is simpler and more efficient, and effectively avoids the risk of damage to the finished product due to improper demolding operation.
[0020] (5) The technology involved in the present invention has more time and economic advantages. On the one hand, the present invention uses raw sand from various sources as the basic material, which is widely available and inexpensive. Chemical modification and coating treatment significantly improve the performance of the raw materials. However, since the amount of chemical modifiers and coating agents used is extremely low and the cost is controllable, chemical modification and coating treatment do not have a significant impact on the price of raw materials. On the other hand, the present invention uses 3D printing technology to make sand core molds, and a core mold of a predetermined shape can be directly obtained without opening an external mold. 3D printing technology provides a high degree of design flexibility, which can easily achieve the manufacturing goal of complex-shaped sand core molds, has better flexibility and convenience, reduces the time and cost of traditional manufacturing mold opening, and has more outstanding time and economic advantages.
[0021] (6) The raw materials of the present invention also have advantages in recycling and reuse and environmental protection. After the carbon fiber composite material of the present invention is formed, the collapsed sand core mold can be directly used in the next cycle after simple drying and screening, which greatly improves the reuse rate of raw materials and reduces resource consumption and raw material procurement costs. From an environmental protection perspective, the unique coated sand preparation and core mold forming process effectively avoids the large-scale generation of waste materials and significantly reduces environmental pressure. The demolding method of water immersion or flushing avoids the use and discharge of chemical solvents, which greatly improves the environmental friendliness of the process. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an electron microscope photo of the raw sand of Example 1 of the present invention;
[0023] Figure 2 This is an electron microscope photo of the modified sand of Example 1 of the present invention;
[0024] Figure 3 This is an electron microscope photo of the coated sand of Example 1 of the present invention;
[0025] Figure 4 This is the XPS spectrum of the raw sand of Example 1 of the present invention;
[0026] Figure 5 This is the XPS spectrum of the modified sand of Example 1 of the present invention;
[0027] Figure 6 This is the XPS spectrum of the coated sand of Example 1 of the present invention;
[0028] Figure 7 FTIR spectra of the original sand, the modified sand containing the catalyst and the coated sand in Example 1 of the present invention;
[0029] Figure 8 It is a moisture regain diagram of the original sand, modified sand and coated sand in Example 1 of the present invention;
[0030] Fig. 9The fluidity diagram of the raw sand and the coated sand of Example 1 of the present invention; in the figure, a is the raw sand, and b is the coated sand;
[0031] Fig.10 This is a particle size distribution diagram of the raw sand in Example 1 of the present invention;
[0032] Fig.11 This is a particle size distribution diagram of the coated sand of Example 1 of the present invention;
[0033] Fig.12 The collapsibility test results of the sand core mold after coating in Example 1 of the present invention;
[0034] Fig.13 This is a physical photo of the product obtained in Example 1 of the present invention; in the figure, a is a sandy core mold, b is a sandy core mold with a composite barrier liquid penetration coating, c is a sandy core mold after coating, and d is a hollow special-shaped carbon fiber composite material;
[0035] Fig.14 Surface roughness of the product obtained in Example 1 of the present invention; in the figure, a is the outer surface of the sandy core mold, b is the outer surface of the sandy core mold with the composite liquid penetration barrier coating, c is the outer surface of the sandy core mold after coating, and d is the inner surface of the hollow carbon fiber composite material;
[0036] Fig.15 The test results of the coating of Example 1 of the present invention in preventing epoxy resin from penetrating and adhering are shown;
[0037] Fig.16 This is a diagram of the printing process of the resin adhesive and the coated sand on a 3D printer according to Example 4 of the present invention; in the figure, a is the printing process, b is the contact between the adhesive sprayed from the nozzle and the coated sand, and c is the sand mold after solidification;
[0038] Fig.17 This is an inkjet image of the resin adhesive in Example 4 of the present invention in the nozzle of a 3D printer. DETAILED DESCRIPTION
[0039] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the present invention.
[0040] The present invention provides a method for forming a hollow special-shaped carbon fiber composite material (hereinafter referred to as the method), characterized in that the method comprises the following steps:
[0041] Step 1: chemically modify the raw sand to arrange the chemical groups and structure on the surface of the raw sand; then wash to remove impurities and unreacted substances on the surface, and then dry to remove moisture to obtain modified sand;
[0042] Preferably, in step 1, the raw sand is raw sand from various sources, preferably silica sand; the particle size of the raw sand is 70 to 140 meshes.
[0043] Preferably, in step 1, the chemical modification is carried out by oxidation modification, surfactant modification or silane coupling agent modification;
[0044] Preferably, in step 1, the oxidation modification specifically comprises: immersing the raw sand in a liquid oxidant solution under stirring for oxidation modification;
[0045] The oxidation modification process is: the stirring speed is 50-100r / min, the modification time is 6-12h, and the modification temperature is room temperature (i.e. 20-35°C);
[0046] The liquid oxidant solution is a mixture of liquid oxidant and water, and its mass fraction is 5-50wt%; the mass of the liquid oxidant is 5-50% of the mass of the original sand;
[0047] The liquid oxidant is at least one of hydrogen peroxide, concentrated nitric acid, dilute nitric acid, concentrated sulfuric acid, permanganic acid, dichromic acid, hypochlorous acid, chloric acid, chlorous acid, perchloric acid and nitrous acid.
[0048] Preferably, in step 1, the surfactant modification specifically comprises: immersing the raw sand in a surfactant solution under stirring to perform surfactant modification;
[0049] The surfactant modification process is: stirring speed is 50-100 r / min, modification time is 6-12 h, and modification temperature is room temperature;
[0050] The surfactant solution is a mixture of surfactant and water, with a mass fraction of 5 to 50 wt%, and the mass of the surfactant accounts for 3 to 10% of the mass of the original sand;
[0051] The surfactant is at least one of cetyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium chloride (DTAC) and cetyltrimethylammonium chloride (CTAC).
[0052] Preferably, in step 1, the process of modifying the silane coupling agent is: preparing a mixed solution with water, ethanol and acid; placing the silane coupling agent in the mixed solution for hydrolysis, and then adding the hydrolyzed silane coupling agent to the raw sand under stirring for silane coupling agent modification, so that the silane coupling agent reacts chemically with the hydroxyl groups on the surface of the silica sand to form a stable Si-O-Si bond, thereby preventing the silica sand particles from agglomerating, so that the silica sand has better fluidity and stacking properties in subsequent applications, thereby improving the strength of the sand mold;
[0053] The mass of water is 0.1-5% of the mass of the original sand, the mass of ethanol is 1-50% of the mass of the original sand, and the mass of acid is 0.1-10% of the mass of ethanol; the pH of the mixed solution is 3-4;
[0054] The acid is an organic acid or an inorganic acid, specifically at least one of acetic acid, oxalic acid, carbonic acid, hydrochloric acid and sulfuric acid;
[0055] The mass of silane coupling agent is 0.1-5% of the mass of original sand;
[0056] The silane coupling agent is at least one of 3-aminopropyl triethoxysilane (KH550), γ-glycidyloxypropyl trimethoxysilane (KH560), γ-methacryloxypropyl trimethoxysilane (KH570), hexadecyl trimethoxysilane (A163), N-(β-aminoethyl)-γ-aminopropyl trimethoxysilane (KH792) and N-β-(aminoethyl)-γ-aminopropyl methyl dimethoxysilane (KH-602);
[0057] The hydrolysis temperature is room temperature and the time is 0.5 to 12 hours;
[0058] The modification process of the silane coupling agent is as follows: the stirring speed is 15-200 r / min, the modification time is 0.5-5h, the modification temperature is 80-150°C, and the stirring device is preferably a drum dryer equipped with a baffle.
[0059] Preferably, in step 1, washing is performed with water; and the drying process is: drying at 60-100° C. for 0.5-2 h.
[0060] Step 2, adding the resin curing catalyst solution to the modified sand, mixing evenly, to obtain modified sand containing the catalyst; then adding the water-soluble polymer, mixing evenly, to obtain a mixed system of the resin curing catalyst solution, the water-soluble polymer and the modified sand; then drying the mixed system while stirring to remove moisture and promote the coordination reaction to be complete, while improving the catalytic activity of the resin curing catalyst, and coating the water-soluble polymer on the surface of the modified sand by utilizing the adsorption and coordination effect of the modified sand on the resin curing catalyst and the coordination effect between the resin curing catalyst and the water-soluble polymer, to obtain coated sand (referred to as coated sand) with a core-shell structure in which the shell layer is the water-soluble polymer and the core layer is the modified sand;
[0061] Preferably, in step 2, the mass fraction of the resin curing catalyst solution is 5 to 40 wt %, and the mass of the resin curing catalyst solution is 0.1 to 5% of the mass of the modified sand;
[0062] The resin curing catalyst is at least one of aluminum chloride, cupric chloride, ferric chloride, zinc chloride, sulfuric acid, phosphoric acid, sulfonic acid, trichloroacetic acid, trifluoroacetic acid and oxalic acid.
[0063] Preferably, in step 2, the resin curing catalyst solution and the modified sand are mixed evenly by stirring, and the stirring process is: stirring speed is 50-400r / min, time is 5-15min, and temperature is room temperature.
[0064] Preferably, in step 2, the mass of the water-soluble polymer is 0.1 to 3% of the mass of the modified sand;
[0065] The water-soluble polymer is at least one of polyethylene glycol powder, polyvinyl pyrrolidone powder and gum arabic powder.
[0066] Preferably, in step 2, the resin curing catalyst solution, the water-soluble polymer and the modified sand are mixed evenly by stirring, and the stirring process is: the stirring speed is 200-400 r / min, the time is 1-10 min, and the temperature is room temperature.
[0067] Preferably, in step 2, the drying while stirring process is: a stirring speed of 15 to 200 r / min, a temperature of 40 to 120° C., and a time of 0.5 to 5 h, preferably in a drum dryer equipped with a baffle.
[0068] Preferably, in step 2, the addition amount of the resin curing catalyst solution and the water-soluble polymer is specifically adjusted according to the specific requirements of the hardness, tensile strength and collapse of the sandy core membrane.
[0069] Preferably, in step 2, the resin curing catalyst solution is added in an atomized manner to make it more evenly dispersed; the water-soluble polymer is added in powder form, which avoids agglomeration due to excessive moisture in the subsequent drying process and makes the coated sand easier to dry.
[0070] Step 3: using the resin adhesive and the coated sand of step 2 as raw materials, a sand core mold is prepared by compression molding or 3D printing;
[0071] Preferably, in step 3, the specific steps of preparing the sand core mold by pressing and molding are: adding a resin adhesive to the coated sand while stirring, and after mixing evenly, evenly filling the coated sand mixed with the resin adhesive into the mold for pressing and molding; then placing the mold in a hot box, and under the action of a coordinated resin curing catalyst in the coated sand, the resin adhesive undergoes a curing reaction, and the coated sand is bonded into a whole, thereby obtaining a sand core mold;
[0072] The stirring process is: stirring speed is 50-400r / min, time is 5-15min, temperature is room temperature;
[0073] The pressing process is: the pressure is 0.01-15 MPa, and the pressing time is 2-10 min;
[0074] The curing reaction temperature is 40 to 120° C. and the time is 0.5 to 6 hours.
[0075] Preferably, in step 3, the specific steps of preparing the sand core mold by 3D printing are: distributing the coated sand to the sanding module of the 3D printer, introducing the resin adhesive into the nozzle of the 3D printer, and in the process of layer-by-layer sanding in the sanding module, the nozzle sprays the resin adhesive layer by layer according to the cross-sectional shape of the part, and under the action of the printer heating system, the coordinated resin curing catalyst in the coated sand promotes the resin adhesive to undergo a curing reaction, so that the coated sand on the cross section of the part is bonded into a whole, and a sand core mold with a complex geometric configuration is obtained;
[0076] The process parameters of 3D printing are: the maximum molding size is 2500×1000×800mm, the printing speed is 27~32s / layer, the printing layer thickness is 0.2~0.5mm, and the number of printing layers and printing time depend on the specific sand core mold size.
[0077] Preferably, in step 3, the mass of the resin adhesive is 0.8-5% of the mass of the coated sand;
[0078] Preferably, in step 3, the resin adhesive is composed of an active agent, a viscosity regulator, a surface tension regulator, a defoaming agent and an antibacterial agent; 60 to 100 parts by mass of the active agent, 1 to 10 parts by mass of the viscosity regulator, 0 to 1 part by mass of the surface tension regulator, 0.1 to 1 part by mass of the defoaming agent, and 0 to 1 part by mass of the antibacterial agent.
[0079] Preferably, in step 3, the active agent is at least one of furfuryl alcohol, 5-hydroxymethylfurfuryl alcohol, 5-nitrofurfuryl alcohol, furfural and furoic acid; the viscosity modifier is at least one of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyethyleneimine, phenolic resin and urea-formaldehyde resin; the surface tension modifier is at least one of silicone oil, sodium dodecyl sulfate and hexadecyltrimethylammonium bromide; the defoamer is at least one of silicone oil defoamer, non-silicone oil defoamer, polyether defoamer and mineral oil defoamer; the antibacterial agent is at least one of sodium benzoate, benzoic acid, methyl parahydroxybenzoate, propyl parahydroxybenzoate, ascorbic acid and tea polyphenols.
[0080] Step 4, compounding a liquid-blocking coating on the outer surface of the sandy core mold in step 3, and then compounding a resin matrix-blocking and adhesion coating on the surface of the liquid-blocking coating to improve the surface structure and roughness of the sandy core mold, and at the same time constructing a coating on the surface of the sandy core mold to block the penetration of liquid resin during the molding of the carbon fiber composite material, to obtain a coated sandy core mold (i.e., a sandy core mold compounded with a liquid-blocking coating and a resin matrix-blocking and adhesion coating);
[0081] Preferably, in step 4, the liquid penetration barrier coating is formed by applying the liquid penetration barrier coating to the outer surface of the sand core mold and drying and curing it;
[0082] The liquid penetration barrier coating is prepared by dispersing ferric oxide particles in ethanol or polyolefin solution; 5 to 20 parts by weight of ferric oxide particles and 20 to 100 parts by weight of ethanol or polyolefin solution;
[0083] The particle size of the ferric oxide particles is 30 to 80 μm;
[0084] The polyolefin solution is prepared by dissolving polyolefin in a mixed solvent of cyclohexane and ethanol; wherein the polyolefin comprises 1 to 5 parts by weight, cyclohexane comprises 50 to 100 parts by weight, and ethanol comprises 0 to 100 parts by weight; the polyolefin is random polypropylene and / or polyolefin elastomer (POE);
[0085] The coating method is brush coating, dipping coating, spraying coating, shower coating or roller coating; the drying temperature is 60-100°C and the drying time is 10-30 minutes.
[0086] Preferably, in step 4, the barrier resin penetration and adhesion coating is formed by applying the barrier resin penetration and adhesion coating to the outer surface of the barrier liquid penetration coating and drying and curing;
[0087] The resin penetration and adhesion barrier coating is made of polyolefin solution or nano-silicon dioxide and polytetrafluoroethylene powder dispersed in polyolefin solution; 1 to 5 parts by mass of nano-silicon dioxide, 1 to 5 parts by mass of polytetrafluoroethylene powder, and 80 to 150 parts by mass of polyolefin solution;
[0088] The particle size of nano-silicon dioxide is 5 to 30 nm, and the particle size of polytetrafluoroethylene powder is 1 to 5 μm;
[0089] The polyolefin solution is prepared by dissolving polyolefin in a mixed solvent of cyclohexane and ethanol; wherein the polyolefin comprises 1 to 5 parts by weight, cyclohexane comprises 50 to 100 parts by weight, and ethanol comprises 0 to 100 parts by weight; the polyolefin is random polypropylene and / or polyolefin elastomer (POE);
[0090] The coating method is brush coating, dipping coating, spraying, shower coating or roller coating; the drying temperature is 40 to 100°C, and the drying time is 10 to 60 minutes.
[0091] Step 5, using the coated sand core mold of step 4 as a molding mold for the carbon fiber composite material, and performing a carbon fiber composite material molding process; after the resin is solidified, soaking or flushing the molding mold with a solvent that can dissolve the water-soluble polymer of step 2 to cause it to collapse and complete the demolding process, thereby obtaining a hollow special-shaped carbon fiber composite material.
[0092] Preferably, in step 5, the carbon fiber composite material forming process adopts winding forming, pultrusion forming, autoclave forming, vacuum bag forming or stamping forming.
[0093] Preferably, in step 5, vacuum bag forming is specifically as follows: neatly wrap the carbon fiber prepreg in a sandy core mold after coating, wrap an isolation film on the carbon fiber prepreg to prevent the carbon fiber prepreg from bonding to the vacuum bag; then place the sandy core film wrapped with the carbon fiber prepreg and the isolation film in a vacuum bag, and then lay a layer of breathable felt on it; then evacuate the vacuum bag to make it close to the carbon fiber prepreg, and apply pressure to it, close the vacuum bag valve, and place it in a hot box, preheat at 40-80°C for 10-30min, and then thermally cure at 100-130°C for 1-2h; then cool to room temperature, take out the sandy core film wrapped with the carbon fiber prepreg and the isolation film from the vacuum bag, tear off the isolation film, and then use a solvent that can dissolve the water-soluble polymer in step 2 to soak or flush the molding mold to make it collapse to complete the demolding process, and obtain a hollow special-shaped carbon fiber composite material.
[0094] Preferably, in step 5, the carbon fiber prepreg is a unidirectional carbon fiber prepreg with a gram weight of 100 to 300 g / m 2 , thickness is 0.1~0.3mm.
[0095] Preferably, in step 5, the solvent capable of dissolving the water-soluble polymer in step 2 is at least one of water, ethanol, isopropanol, N,N-dimethylformamide, N,N-dimethylacetamide and dichloromethane, preferably water.
[0096] In the embodiment, the test method is as follows: (1) observing the surface morphology on a Phenom XL desktop scanning electron microscope; (2) using a NEXSA X-ray photoelectron spectrometer to test the content and changes of elements; (3) using a Nicolet iS50 Fourier transform infrared spectrometer to analyze the changes in chemical bonds; (4) testing the moisture regain in an LHS-100SC constant temperature and humidity chamber; (5) determining the fluidity based on the angle of repose method: a sand pile is formed by free falling from a height of 10 cm at a speed of 20 g per second, and its angle of repose θ is measured; (6) using a Mastersizer 3000 laser particle size analyzer to analyze the size and distribution of sand particles; (7) detecting the viscosity of the adhesive on an MCR302 modular intelligent advanced rheometer; (8) analyzing the surface tension of the adhesive on a DSA30S fully automatic contact angle tester; (9) using an OLS4100 laser confocal microscope to test the surface roughness and line roughness of the product ( Fig.14); (10) Using the laboratory TR220 surface roughness tester to test the linear roughness of the product; (11) Using the ASKY industrial-grade 3D printer to test the printing and molding of the adhesive and the coated sand; (12) Using the ASKY inkjet system to test the inkjet condition of the adhesive in the industrial-grade 3D printer nozzle.
[0097] Embodiment 1:
[0098] Step 1, add 70-140 mesh raw sand and a hydrogen peroxide aqueous solution (mass fraction of 10wt%) with the same mass as the raw sand into a sand mixer, so that the hydrogen peroxide aqueous solution completely immerses the raw sand, stirs at a speed of 100r / min at room temperature for 4h, then repeatedly washes with water, and after washing, places in an oven at 100°C for 2h to dry it completely to obtain modified sand;
[0099] Step 2, adding the modified sand to the sand mixer, at a stirring speed of 400r / min, evenly dispersing 0.5% of the aluminum chloride solution (mass fraction of 31.2wt%) of the modified sand in the modified sand in an atomized manner, and the stirring time is 10min; then, at a stirring speed of 400r / min, fully mixing 0.375% of the polyvinyl pyrrolidone powder of the modified sand with the modified sand containing the catalyst, and the stirring time is 10min; then, transferring the mixed system to a drum dryer equipped with a baffle, drying at 100°C for 1h, and obtaining coated sand;
[0100] Step 3, placing the coated sand in a sand mixer, adding 2.5% of the mass of the coated sand (composed of 97 parts by mass of furfuryl alcohol, 3 parts by mass of polyvinyl pyrrolidone and 0.2 parts by mass of silicone oil defoamer) to the coated sand at a stirring speed of 400r / min, taking it out after stirring for 10 minutes, filling the coated sand mixed with the resin adhesive evenly into the mold to be pressed into a sand mold of a specific shape, and then placing it in an oven and heating it at 80°C for 4h, causing the resin adhesive to undergo a curing reaction under the catalytic action of aluminum chloride, bonding the coated sand into a sandy core mold with a complex geometric configuration, and using the method in the national standard GB 13022-91 to make a corresponding eight-shaped block for performance testing;
[0101] Step 4: Compound a layer of liquid penetration barrier coating (composed of 1 part by mass of ferric oxide particles and 5 parts by mass of ethanol) on the surface of the sandy core mold obtained in step 3, and heat it at 100° C. for 10 minutes to dry and solidify; then compound a layer of barrier resin penetration and adhesion coating (made by dissolving 3 parts by mass of POE in 97 parts by mass of cyclohexane), and heat it at 100° C. for 1 hour to dry and solidify, to obtain a coated sandy core mold;
[0102] Step 5, using the sandy core mold obtained in step 4 as a supporting mold, neatly wrap the carbon fiber prepreg in the coated sandy core mold, wrap an isolation film on the carbon fiber prepreg to prevent the carbon fiber prepreg from bonding to the vacuum bag; then place the sandy core membrane wrapped with the carbon fiber prepreg and the isolation film in a vacuum bag, and then lay a layer of breathable felt on it; then evacuate the vacuum bag to make it close to the carbon fiber prepreg, and apply pressure to it, close the vacuum bag valve, and place it in a hot box, preheat at 80°C for 30 minutes, and then heat cure at 130°C for 1 hour; then cool to room temperature, take out the sandy core membrane wrapped with the carbon fiber prepreg and the isolation film from the vacuum bag, tear off the isolation film, and then use water to disperse the sandy core membrane to complete the demolding process to obtain a hollow special-shaped carbon fiber composite material with a smooth surface.
[0103] Depend on Figure 1 , 2 3. It can be seen that compared with the original sand, the surface mud content of the modified sand obtained in step 1 is significantly reduced, forming a rough surface structure that is conducive to film coating. Compared with the modified sand, the coated sand obtained in step 2 has a smoother surface, indicating that the coating layer can further optimize the surface structure of the original sand.
[0104] Depend on Figure 4 , 5 6, it can be seen that compared with the original sand, the number of hydroxyl groups on the surface of the modified sand obtained in step 1 is significantly increased. The XPS spectrum of the coated sand obtained in step 2 shows the O1s peak of C=O in the polymer, proving that the coating is successful.
[0105] Depend on Figure 7 It can be seen that compared with the modified sand containing catalyst, the coated sand does not show the OH absorption peak. At the same time, the coated sand shows the absorption peak of C=O in the polymer and the absorption peak of the polymer-metal ion coordination bond, further indicating the formation of a coating layer.
[0106] Depend on Figure 8 It can be seen that under the conditions of temperature 30°C and humidity 70%, the moisture regain of coated sand has not increased significantly compared with original sand and modified sand.
[0107] Depend on Fig. 9 It can be seen that the repose angles of coated sand and original sand are close and extremely low, indicating that the coating does not affect the fluidity of the sand.
[0108] Depend on Fig.10 , 11 It can be seen that the coated sand and the original sand have the same particle size and distribution, indicating that the coating process did not significantly change the particle size and distribution of the sand, which provides convenience for subsequent applications.
[0109] Under the bonding effect of the resin adhesive and the coating layer, the hardness of the eight-shaped block obtained in step 3 is 54.5HD, and the tensile strength is 2.44MPa. The hardness and tensile strength of the sand mold are good, and the sand does not fall off, which is higher than the strength standard of the printed part. It can be used for the support mold of carbon fiber composite materials. At the same time, the coating layer is water-soluble, and the sand mold can quickly collapse in water (such as Fig.12 The moisture regain of the eight-shaped block obtained in step 3 is 0.11% when placed in an environment of 28°C and 60% humidity for one day. After moisture regain, the tensile strength drops to 0.94MPa. After drying, the strength can still be restored to the initial value.
[0110] Depend on Fig.14 It can be seen that the surface roughness of the sand core mold obtained in step 3 is 35.5 μm, and the surface roughness of the sand core mold after coating obtained in step 4 is reduced to 7.5 μm, the surface flatness and smoothness are improved, and the surface can block liquids such as epoxy resin (such as Fig.15 As shown, a is a sand core mold with only a liquid penetration barrier coating, b is a sand core mold after coating, and c is the adhesion between the surfaces of products a and b and the resin. It can be seen from Figure c that after the resin is cured, the cured resin on product b can be completely peeled off, while the cured resin on product a cannot be peeled off), which provides convenience for demolding carbon fiber composite material special-shaped parts and ensuring the smooth surface of carbon fiber composite materials.
[0111] The surface roughness of the inner surface of the carbon fiber composite material obtained after demoulding is 2.2 μm, and the tensile strength of the carbon fiber composite material is 78 MPa.
[0112] Embodiment 2:
[0113] This embodiment is the same as embodiment 1, except that: in step 2, the polyvinyl pyrrolidone powder is replaced by polyethylene glycol (molecular weight 20,000) powder; in step 3, the composition of the resin adhesive is 98 parts by mass of furfuryl alcohol, 2 parts by mass of polyethylene glycol (molecular weight 20,000), and 0.2 parts by mass of silicone oil defoamer.
[0114] The hardness of the eight-shaped block obtained in step 3 is 44.0HD, and the tensile strength is 2.02MPa. The moisture regain of the eight-shaped block obtained in step 3 is 0.09% when placed in an environment of temperature 28°C and humidity 60% for one day, and the tensile strength drops to 0.65MPa after moisture regain. It can be seen that the changes in the type of coating polymer and the resin adhesive component will significantly affect the hardness and strength of the sandy core film, and then affect the carbon fiber composite material molding process. Despite this, the tensile strength of the carbon fiber composite material still reaches 77Mpa, indicating that the sandy core mold is suitable for carbon fiber composite material molding.
[0115] Embodiment 3:
[0116] This embodiment is the same as embodiment 1, except that: in step 2, the polyvinyl pyrrolidone powder is replaced by polyethylene glycol (molecular weight 2000) powder; in step 3, the composition of the resin adhesive is 98 parts by mass of furfuryl alcohol, 2 parts by mass of polyethylene glycol (molecular weight 2000), and 0.2 parts by mass of silicone oil defoamer.
[0117] The hardness of the eight-shaped block obtained in step 3 is 42.8HD, and the tensile strength is 1.92MPa. The moisture regain of the eight-shaped block obtained in step 3 is 0.13% when placed in an environment of temperature 28°C and humidity 60% for one day, and the tensile strength drops to 0.83MPa after moisture regain. It can be seen that the changes in the molecular weight of the coating polymer and the molecular weight of the components in the resin adhesive will significantly affect the hardness and strength of the sandy core film, and then affect the carbon fiber composite material molding process. Despite this, the tensile strength of the carbon fiber composite material still reaches 76Mpa, indicating that the sandy core mold is suitable for carbon fiber composite material molding.
[0118] Embodiment 4:
[0119] This embodiment is the same as Embodiment 1, except that: Step 3 is specifically: distributing the coated sand to the sanding module of the 3D printer, introducing a resin adhesive (composed of 97 parts by mass of furfuryl alcohol, 3 parts by mass of polyvinyl pyrrolidone and 0.2 parts by mass of a silicone oil defoamer) into the nozzle of the 3D printer, and in the process of layer-by-layer sanding of the sanding module of the 3D printer, the nozzle of the 3D printer sprays the resin adhesive layer by layer according to the cross-sectional shape of the part, and under the action of the printer heating system, aluminum chloride catalyzes the curing reaction of the resin adhesive, and the coated sand with a core-shell structure on the cross-section of the part is bonded into a whole, so as to obtain a sandy core mold with a complex geometric configuration.
[0120] The viscosity of the resin adhesive in step 3 is 10.8mpa·s, and the surface tension is 36.8mN / m, which meets the requirements of industrial-grade 3D printer nozzles. Fig.16 It can be seen that the coated sand is in good condition. After the adhesive contacts the coated sand, the coordinated aluminum chloride in the coating layer catalyzes the adhesive to undergo a curing reaction. The cured adhesive bonds the coated sand into an integral structure through point bonding. Fig.17 It can be seen that the resin adhesive in step 3 has good inkjet performance during the actual printing process and is suitable for actual printing.
[0121] The hardness of the eight-shaped block obtained in step 3 is 45HD, and the tensile strength is 2.0MPa. The moisture regain of the eight-shaped block obtained in step 3 is only 0.08% after being placed in an environment with a temperature of 28°C and a humidity of 60% for one day, and the tensile strength drops to 1.2MPa after moisture regain; it can be seen that the adhesive and coated sand designed by the present invention meet the printing requirements of industrial-grade 3D printers, and the printed sand core film can be used for the molding of hollow special-shaped carbon fiber composite materials, and the uniqueness of 3D printing technology in molding complex-configuration sand core films can provide a variety of mold supports for the molding of carbon fiber composite materials, and can achieve the goal of one-time molding of complex-configuration carbon fiber composite materials.
[0122] Embodiment 5:
[0123] This embodiment is the same as embodiment 1, except that in step 4, the composition of the liquid penetration barrier coating is 1 part by mass of ferric oxide particles and 5 parts by mass of polyolefin solution, and the composition of the resin penetration and adhesion barrier coating is 1 part by mass of nano-silicon dioxide, 2 parts by mass of polytetrafluoroethylene powder and 97 parts by mass of polyolefin solution.
[0124] The linear roughness of the coated sandy core mold obtained in step 4 is reduced from 3.5 μm to 2.7 μm, and the linear roughness of the inner surface of the carbon fiber composite material formed by the sandy core membrane is reduced from 0.9 μm in Example 1 to 0.8 μm. It can be seen that by optimizing the coating system, a sandy core membrane with a smoother surface can be obtained, and at the same time, a high-quality carbon fiber composite material product with a smoother surface can be obtained.
[0125] Comparative Example 1:
[0126] The only difference between this comparative example and Example 1 is that in step 1, no chemical modification of the raw sand is performed.
[0127] The results show that the hardness of the splayed block obtained by steps 1 and 2 of this comparative example is 50.5HD, and the tensile strength is 2.3MPa, which are far inferior to the performance of the splayed block obtained by steps 1, 2, and 3 of Example 1. The moisture regain of the splayed block obtained by steps 1 and 2 of this comparative example is 0.15% in 24 hours, and the tensile strength of the splayed block after moisture regain decreases to 0.6MPa, which is also lower than the performance of the splayed block obtained by steps 1, 2, and 3 of Example 1. It can be seen that chemical modification is extremely important for improving the performance of the sand mold, that is, the chemical modification step cannot be omitted.
[0128] Comparative Example 2:
[0129] The only difference between this comparative example and Example 1 is that no polyvinyl pyrrolidone powder is added in step 2.
[0130] The results showed that the sand core film could not be collapsed by flushing or soaking it with tap water and applying a certain external force (e.g. Fig.12As shown), the demoulding of the hollow special-shaped carbon fiber composite material becomes a problem, which limits its molding. It can be seen that the polymer coating is extremely important for the water disintegration of the sandy core membrane and the subsequent demoulding of the carbon fiber composite material, that is, the polymer coating step cannot be omitted. At the same time, the hardness of the eight-shaped block obtained by steps 1, 2, and 3 of this comparative example is 41.5HD, and the tensile strength is 1.8MPa, which is far less than the performance of the eight-shaped block obtained by steps 1 and 2 of comparative example 1 and steps 1, 2, and 3 of embodiment 1. It can be seen that the polymer coating is also extremely beneficial for improving the strength of the sand mold, and the high-strength sandy core membrane brings great convenience to the subsequent carbon fiber molding operation.
[0131] Comparative Example 3:
[0132] The only difference between this comparative example and Example 1 is that in step 4, no barrier resin penetration and adhesion coating is used.
[0133] The results show that during the water collapse demoulding process, the carbon fiber composite material adheres to the surface of the sand core mold, resulting in sand sticking to the inner surface of the hollow carbon fiber composite material, affecting the surface finish and greatly reducing the quality of the finished product. It can be seen that barrier resin penetration and adhesion coating are extremely effective in blocking resin infiltration during the molding process of carbon fiber composites, which can assist water in achieving the goal of clean demoulding and at the same time give the carbon fiber composite material a smooth surface. Therefore, the step of barrier resin penetration and adhesion coating treatment is also crucial and cannot be omitted.
[0134] Comparative Example 4:
[0135] The only difference between this comparative example and Example 4 is that the resin adhesive in step 2 is furfuryl alcohol.
[0136] The results show that when the resin adhesive is only furfuryl alcohol, its viscosity is only 4.9mpa·s, while its surface tension reaches 42mN / m, which does not meet the requirements of industrial-grade 3D printer nozzles (viscosity of 6-12mpa·s and surface tension of 25-40mN / m). Therefore, the continuity of inkjet printing is affected during printing, there is serious ink accumulation, and the strength and precision of the printed product are greatly reduced, which in turn affects the subsequent molding of carbon fiber composite materials. It can be seen that the design of the adhesive system is extremely important to ensure the smooth progress of the 3D printing process.
[0137] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A method for forming a hollow special-shaped carbon fiber composite material, characterized in that: The method comprises the following steps: Step 1: chemically modify the raw sand to arrange the chemical groups and structure on the surface of the raw sand; then wash to remove impurities and unreacted substances on the surface, and then dry to obtain modified sand; Step 2, adding the resin curing catalyst solution to the modified sand, mixing evenly, to obtain modified sand containing the catalyst; then adding the water-soluble polymer, mixing evenly, to obtain a mixed system of the resin curing catalyst solution, the water-soluble polymer and the modified sand; then drying the mixed system while stirring to remove moisture and promote the coordination reaction to be complete, while improving the catalytic activity of the resin curing catalyst, and coating the surface of the modified sand with the water-soluble polymer to obtain coated sand with a core-shell structure in which the shell layer is the water-soluble polymer and the core layer is the modified sand; Step 3: using the resin adhesive and the coated sand of step 2 as raw materials, a sand core mold is prepared by compression molding or 3D printing; Step 4, compounding a liquid penetration barrier coating on the outer surface of the sandy core mold in step 3, and then compounding a resin matrix penetration barrier and adhesion barrier coating on the surface of the liquid penetration barrier coating to improve the surface structure and roughness of the sandy core mold, and at the same time constructing a coating on the surface of the sandy core mold to prevent liquid resin from penetrating during molding of the carbon fiber composite material, thereby obtaining a coated sandy core mold; Step 5, using the coated sand core mold of step 4 as a molding mold for the carbon fiber composite material, and performing a carbon fiber composite material molding process; after the resin is solidified, using a solvent that can dissolve the water-soluble polymer of step 2 to collapse the molding mold, completing the demolding process, and obtaining a hollow special-shaped carbon fiber composite material.
2. The method for forming a hollow special-shaped carbon fiber composite material according to claim 1, characterized in that: In step 1, the raw sand is from various sources; the particle size of the raw sand is 70-140 meshes; In step 1, the chemical modification adopts oxidation modification, surfactant modification or silane coupling agent modification; In step 1, washing is performed with water; the drying process is: drying at 60-100° C. for 0.5-2 h.
3. The method for forming a hollow special-shaped carbon fiber composite material according to claim 2, characterized in that: In step 1, the oxidation modification specifically comprises: immersing the raw sand in a liquid oxidant solution under stirring for oxidation modification; The oxidation modification process is: stirring speed is 50-100r / min, modification time is 6-12h, and modification temperature is room temperature; The liquid oxidant solution is a mixture of liquid oxidant and water, with a mass fraction of 5 to 50 wt %; the mass of the liquid oxidant is 5 to 50 % of the mass of the original sand; The liquid oxidant is at least one of hydrogen peroxide, concentrated nitric acid, dilute nitric acid, concentrated sulfuric acid, permanganic acid, dichromic acid, hypochlorous acid, chloric acid, chlorous acid, perchloric acid and nitrous acid; In step 1, the surfactant modification specifically comprises: immersing the raw sand in a surfactant solution under stirring to perform surfactant modification; The surfactant modification process is: stirring speed is 50-100 r / min, modification time is 6-12 h, and modification temperature is room temperature; The surfactant solution is a mixture of surfactant and water, with a mass fraction of 5 to 50 wt%, and the mass of the surfactant accounts for 3 to 10% of the mass of the original sand; The surfactant is at least one of CTAB, DTAC and CTAC; In step 1, the process of silane coupling agent modification is: preparing a mixed solution with water, ethanol and acid; placing the silane coupling agent in the mixed solution for hydrolysis, and then adding the hydrolyzed silane coupling agent to the raw sand under stirring for silane coupling agent modification; The mass of water is 0.1-5% of the mass of the original sand, the mass of ethanol is 1-50% of the mass of the original sand, and the mass of acid is 0.1-10% of the mass of ethanol; the pH of the mixed solution is 3-4; The acid is at least one of acetic acid, oxalic acid, carbonic acid, hydrochloric acid and sulfuric acid; The mass of silane coupling agent is 0.1-5% of the mass of original sand; The silane coupling agent is at least one of KH550, KH560, KH570, A163, KH792 and KH-602; The hydrolysis temperature is room temperature and the time is 0.5 to 12 hours; The modification process of silane coupling agent is: stirring speed is 15-200r / min, modification time is 0.5-5h, and modification temperature is 80-150℃.
4. The method for forming a hollow special-shaped carbon fiber composite material according to claim 1, characterized in that: In step 2, the mass fraction of the resin curing catalyst solution is 5 to 40 wt %, and the mass of the resin curing catalyst solution is 0.1 to 5% of the mass of the modified sand; In step 2, the resin curing catalyst solution and the modified sand are mixed evenly by stirring, and the stirring process is: stirring speed is 50-400r / min, time is 5-15min, and temperature is room temperature; In step 2, the mass of the water-soluble polymer is 0.1 to 3% of the mass of the modified sand; In step 2, the resin curing catalyst solution, the water-soluble polymer and the modified sand are mixed evenly by stirring, and the stirring process is: the stirring speed is 200-400 r / min, the time is 1-10 min, and the temperature is room temperature; In step 2, the drying process while stirring is: the stirring speed is 15 to 200 r / min, the temperature is 40 to 120° C., and the time is 0.5 to 5 h; In step 2, the resin curing catalyst solution is added in an atomized manner to make it more evenly dispersed; the water-soluble polymer is added in powder form, which avoids agglomeration due to excessive moisture in the subsequent drying process and makes the coated sand easier to dry.
5. The method for forming a hollow special-shaped carbon fiber composite material according to claim 1 or 4, characterized in that: In step 2, the resin curing catalyst is at least one of aluminum chloride, cupric chloride, ferric chloride, zinc chloride, sulfuric acid, phosphoric acid, sulfonic acid, trichloroacetic acid, trifluoroacetic acid and oxalic acid; and the water-soluble polymer is at least one of polyethylene glycol, polyvinyl pyrrolidone and gum arabic.
6. The method for forming a hollow special-shaped carbon fiber composite material according to claim 1, characterized in that: In step 3, the specific steps of preparing the sand core mold by pressing and molding are: adding the resin adhesive to the coated sand while stirring, and after mixing evenly, evenly filling the coated sand mixed with the resin adhesive into the mold for pressing and molding; then, under the action of the coordinated resin curing catalyst in the coated sand, the resin adhesive undergoes a curing reaction, and the coated sand is bonded into a whole to obtain a sand core mold; The stirring process is: stirring speed is 50-400r / min, time is 5-15min, temperature is room temperature; The pressing process is: the pressure is 0.01-15 MPa, and the pressing time is 2-10 min; The curing reaction temperature is 40-120°C and the time is 0.5-6h; In step 3, the specific steps of preparing the sand core mold by 3D printing are: distributing the coated sand to the sand laying module of the 3D printer, introducing the resin adhesive into the nozzle of the 3D printer, and in the process of layer-by-layer sand laying in the sand laying module, the nozzle sprays the resin adhesive layer by layer according to the cross-sectional shape of the part, and under the action of the printer heating system, the coordinated resin curing catalyst in the coated sand promotes the resin adhesive to undergo a curing reaction, so that the coated sand on the cross section of the part is bonded into a whole, and a sand core mold with a complex geometric configuration is obtained; The process parameters of 3D printing are: maximum molding size is 2500×1000×800mm, printing speed is 27~32s / layer, and printing layer thickness is 0.2~0.5mm.
7. The method for forming a hollow special-shaped carbon fiber composite material according to claim 1, characterized in that: In step 3, the mass of the resin adhesive is 0.8-5% of the mass of the coated sand; In step 3, the resin adhesive is composed of an active agent, a viscosity modifier, a surface tension modifier, a defoamer and an antibacterial agent; 60 to 100 parts by weight of the active agent, 1 to 10 parts by weight of the viscosity modifier, 0 to 1 part by weight of the surface tension modifier, 0.1 to 1 part by weight of the defoamer, and 0 to 1 part by weight of the antibacterial agent; In step 3, the active agent is at least one of furfuryl alcohol, 5-hydroxymethylfurfuryl alcohol, 5-nitrofurfuryl alcohol, furfural and furoic acid; the viscosity modifier is at least one of polyvinyl pyrrolidone, polyethylene glycol, polyvinyl alcohol, polyethyleneimine, phenolic resin and urea-formaldehyde resin; the surface tension modifier is at least one of silicone oil, sodium dodecyl sulfate and hexadecyltrimethylammonium bromide; the defoamer is at least one of silicone oil defoamer, non-silicone oil defoamer, polyether defoamer and mineral oil defoamer; the antibacterial agent is at least one of sodium benzoate, benzoic acid, methyl parahydroxybenzoate, propyl parahydroxybenzoate, ascorbic acid and tea polyphenols.
8. The method for forming a hollow special-shaped carbon fiber composite material according to claim 1, characterized in that: In step 4, the liquid penetration barrier coating is formed by applying the liquid penetration barrier coating to the outer surface of the sand core mold and drying and curing it; The liquid penetration barrier coating is prepared by dispersing ferric oxide particles in ethanol or polyolefin solution; 5 to 20 parts by weight of ferric oxide particles and 20 to 100 parts by weight of ethanol or polyolefin solution; The particle size of the ferric oxide particles is 30 to 80 μm; The polyolefin solution is prepared by dissolving polyolefin in a mixed solvent of cyclohexane and ethanol; wherein the polyolefin comprises 1 to 5 parts by weight, cyclohexane comprises 50 to 100 parts by weight, and ethanol comprises 0 to 100 parts by weight; the polyolefin is random polypropylene and / or polyolefin elastomer; The coating method is brush coating, dipping coating, spraying coating, shower coating or roller coating; the drying temperature is 60-100°C and the drying time is 10-30 minutes.
9. The method for forming a hollow special-shaped carbon fiber composite material according to claim 1, characterized in that: In step 4, the barrier resin penetration and adhesion coating is formed by applying the barrier resin penetration and adhesion coating to the outer surface of the barrier liquid penetration coating and drying and curing it; The resin penetration and adhesion barrier coating is made of polyolefin solution or nano-silicon dioxide and polytetrafluoroethylene powder dispersed in polyolefin solution; 1 to 5 parts by mass of nano-silicon dioxide, 1 to 5 parts by mass of polytetrafluoroethylene powder, and 80 to 150 parts by mass of polyolefin solution; The particle size of nano-silicon dioxide is 5 to 30 nm, and the particle size of polytetrafluoroethylene powder is 1 to 5 μm; The polyolefin solution is prepared by dissolving polyolefin in a mixed solvent of cyclohexane and ethanol; wherein the polyolefin comprises 1 to 5 parts by weight, cyclohexane comprises 50 to 100 parts by weight, and ethanol comprises 0 to 100 parts by weight; the polyolefin is random polypropylene and / or polyolefin elastomer; The coating method is brush coating, dipping coating, spraying, shower coating or roller coating; the drying temperature is 40 to 100°C, and the drying time is 10 to 60 minutes.
10. The method for forming a hollow special-shaped carbon fiber composite material according to claim 1, characterized in that: In step 5, the solvent capable of dissolving the water-soluble polymer in step 2 is at least one of water, ethanol, isopropanol, N,N-dimethylformamide, N,N-dimethylacetamide and dichloromethane.
Citation Information
Patent Citations
Composite lattice structure and preparation method
CN107599445A
Machining method of special-shaped hollow structure composite part molding mandrel
CN109895418A
High-performance large-tow carbon fiber composite material and preparation method thereof
CN112961464A
Hollow beam made of carbon fiber composite material as well as preparation method and application of hollow beam
CN118144313A
Process for producing hollow bodies comprising fibre-reinforced ceramic materials
US20030118757A1